2005
DOI: 10.1371/journal.pgen.0020004.eor
|View full text |Cite
|
Sign up to set email alerts
|

The Notch ligand JAG1 is required for sensory progenitor development in the mammalian inner ear

Abstract: In mammals, six separate sensory regions in the inner ear are essential for hearing and balance function. Each sensory region is made up of hair cells, which are the sensory cells, and their associated supporting cells, both arising from a common progenitor. Little is known about the molecular mechanisms that govern the development of these sensory organs. Notch signaling plays a pivotal role in the differentiation of hair cells and supporting cells by mediating lateral inhibition via the ligands Delta-like 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
132
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(140 citation statements)
references
References 47 publications
8
132
0
Order By: Relevance
“…AB5603) and used at 1:1000. This antibody has been used on mouse (Ferri et al 2004;Kiernan et al 2006), and Western blot analyses carried out by the manufacturer on murine samples demonstrated that this antibody, at lower concentrations, recognizes a single protein of the correct size, approximately 34 kDa. The second anti-Sox2 antibody, an affinity purified goat polyclonal antibody directed against the C-terminus of human Sox2, was purchased from Santa Cruz (Sox-2 Y-17, Cat.…”
Section: Antibodiesmentioning
confidence: 99%
See 4 more Smart Citations
“…AB5603) and used at 1:1000. This antibody has been used on mouse (Ferri et al 2004;Kiernan et al 2006), and Western blot analyses carried out by the manufacturer on murine samples demonstrated that this antibody, at lower concentrations, recognizes a single protein of the correct size, approximately 34 kDa. The second anti-Sox2 antibody, an affinity purified goat polyclonal antibody directed against the C-terminus of human Sox2, was purchased from Santa Cruz (Sox-2 Y-17, Cat.…”
Section: Antibodiesmentioning
confidence: 99%
“…Western blot analyses carried out by the manufacturer on murine samples have demonstrated that this antibody, as well as the anti-Jagged1 (C-20) antibody discussed below, does not cross-react and recognizes a single protein of the correct size (150 kDa molecular weight). Others have used the H-114 antibody in mouse inner ear (Zine and de Ribaupierre 2002;Woods et al 2004;Kiernan et al 2006;Jones et al 2006). Jagged1 is an affinity purified goat polyclonal antibody raised against the C-terminus of human Jagged1.…”
Section: Antibodiesmentioning
confidence: 99%
See 3 more Smart Citations